Report on industrial attachment with Philips Electronics Singapore (DAP) maintenance department - Koh, Tiong Aik. (2008)
During the attachment, author was introduced to the complete process required in the making of an electric iron. The making of the heating element was studied in detail and will be the main focus of this report.